2016
DOI: 10.1016/j.ijrobp.2015.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Very High-Risk Localized Prostate Cancer: Outcomes Following Definitive Radiation

Abstract: Purpose/Objectives Existing definitions of high-risk prostate cancer comprise men who experience significant heterogeneity in outcomes. As such, criteria that identify a subpopulation of NCCN high-risk prostate cancer patients who are at very high risk (VHR) for poor survival outcomes following prostatectomy were recently developed at our institution and include the presence of any of the following disease characteristics: multiple NCCN high-risk factors, primary Gleason pattern 5 disease, and/or ≥5 biopsy cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 48 publications
0
23
1
1
Order By: Relevance
“…In contrast to our findings, Narang et al showed that when evaluating patients with HR disease who were treated over a 15 year interval from 1993 to 2006, the revised 2015 NCCN HR/VHR subgrouping were predictive for worse outcomes in the VHR subgroup [6]. Although the long follow-up interval is an important strength of Narang’s study, the median follow-up time of our cohort is 50 m (range: 12 m-142 m) and the median time to BF in our reports are similar at 34 m and 30 m. The difference in our findings may be better explained by the differences in treatment received by our respective cohorts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, Narang et al showed that when evaluating patients with HR disease who were treated over a 15 year interval from 1993 to 2006, the revised 2015 NCCN HR/VHR subgrouping were predictive for worse outcomes in the VHR subgroup [6]. Although the long follow-up interval is an important strength of Narang’s study, the median follow-up time of our cohort is 50 m (range: 12 m-142 m) and the median time to BF in our reports are similar at 34 m and 30 m. The difference in our findings may be better explained by the differences in treatment received by our respective cohorts.…”
Section: Discussioncontrasting
confidence: 99%
“…In consideration of these findings, the 2014 NCCN guidelines were revised and added the presence of primary Gleason grade 5 or ≥5 cores with Gleason score 8–10 as new criteria for inclusion into the VHR group [1]. While relevant for surgical outcomes, the predictive value of the HR/VHR grouping has not been assessed in patients treated with current CRT techniques [6]. Recently, Narang et al showed inferior outcomes in the VHR versus HR group in a cohort of patients treated with RT and ADT from 1993 through 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Subsequently, VHR criteria were shown to also identify men with markedly higher rates of METS and PCa-specific mortality in a cohort treated with definitive radiation therapy (RT) plus androgen deprivation therapy (ADT). 11 Cancer February 1, 2019 Here we sought to determine whether VHR criteria retain prognostic significance in a validation study by pooling patients with high-risk PCa who underwent RP at 3 independent tertiary centers.…”
Section: Introductionmentioning
confidence: 99%
“…Warde et al [10] randomized 1,205 patients between RT plus ADT and ADT only, and showed that RT plus ADT improved overall survival at 7-year follow-up compared with ADT only (74 vs. 66%). A number of retrospective studies have shown results that favor RT over RP, with Narang et al [11 ]showing lower PCSM (24 vs. 38% in a total of 214 patients) (table 1) and Stephans et al [12] indicating lower BCR rates (46 vs. 53% in a total of > 1,500 patients). Moreover, concerns about side effects, positive margins, and inadequate disease control in high-risk patients may contribute to a ‘therapeutic nihilism' that sways physicians away from recommending RP and towards RT plus ADT for patients with high-risk PC [13].…”
Section: Radiation Therapymentioning
confidence: 99%